Pengertian Islam Dan Sains Menurut Sayyed Nasr - Rohematus Sya’diah; Noviana Putri; Tasya Arnita; Alfina Wildatul Fitriyah (Pusat Riset dan Inovasi Nasional, 2024)
Syed Nashr is one of the leading intellectuals in the discourse on the relationship between science and religion, especially in the Islamic world. Examining Nashr's thought is a relevant and significant effort to better understand one important aspect of scientific development in the Islamic world in particular, and science in general in the West. This research uses a qualitative descriptive research method by comparing books, journals, articles and others which reveal the meaning of science and religion and the relationship between the two according to Syed Nashr as one of the Muslim scientists who is aggressive towards science. From the analysis carried out by Syed Nashr, it is revealed that modern Western science is experiencing a spiritual crisis and is experiencing disease infection by secular modern thinking, therefore science needs an infusion or injection of Islamic values ​​with a divine dimension in religious revelation so that science and religion there can be a balance between the worldly and the spiritual and all of this must be based on the phrase ''Laa ilaa hailla Allah'' For the purpose of Nasr providing these thoughts to explore Nasr's thoughts regarding the definition of religion and science, as well as how these two disciplines can complement each other and be harmonious in the pursuit of truth.